PENGARUH METODE PEMBELAJARAN MICROLEARNING BERBANTUAN MEDIA VIDEO TUTORIAL TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS Vll SMPN 7 KISARAN - Aulia Fitri; Mapilindo Mapilindo (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The Effect of Microlearning Assisted by Video Tutorials on the Writing Skills of Procedural Text at VIIth-Grade Students of SMP Negeri 7 Kisaran. Skripsi. Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Asahan University. Advisor: Drs. Mapilindo, M.Pd. The study aims to determine the effect of microlearning assisted by video tutorials on the writing skills at VIIth-grade students of SMP Negeri 7 Kisaran. This study used a quantitative approach with an experimental method and a posttest-only control group design. The study sample consisted of an experimental class and a control class. Data collection was conducted through a test of procedural text writing skills before and after the treatment. The results showed that the use of microlearning assisted by video tutorials had a significant effect on the writing skills of seventh-grade students. This is evident from the higher average score of the experimental class compared to the control class. The experimental class obtained an average score of 83.17, categorized as good, while the control class obtained an average score of 69.42, categorized as sufficient. The results of the normality test showed that the data were normally distributed, and the homogeneity test showed that both groups had homogeneous variances. Based on the hypothesis test results, the calculated t value was greater than the t table, so the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.